Lithic devotionality and other aesthetic strata: Buddhist garden shrines in rural Java. Issue 4 (2nd October 2022) - Rizzo, Roberto
Abstract: In this article I explore the contemporary practice of establishing garden shrines in Buddhist rural Java. While on the surface the placement of shrines follows the demands of environmental upgrading and beautification strategies, often in accord with eco-tourist imaginaries, the practice reveals a complex aggregation of material and discursive threads. The article situates the project, ethnographically, as a sensorial practice in which environmental awareness and a sense of "atmosphere" are directly involved. This perceptual domain, particularly the relationship of the villagers to the Sakyamuni statuettes, is simultaneously articulated in continuity with the religious field of Javanese Buddhism, as it encompasses notions of sacralization and rituality. I recover the idea of aesthetic practice in order to bring these sensorial stems on a common platform. In blending discursive and materialist approaches, the article converses with the idea of strata as devised by Deleuze and Guattari as a pivotal image in their work on rhizomes. Through the concept of stratification, I argue, it is possible to apprehend Buddhist shrines as cultural formations in which "everything is involved, " that is, as multiplicities in which layers of materiality and discourse are intertwined in meaningful and generative ways.